Energy transfer in colloidal CdTe quantum dot nanoclusters - Bradley, Louise; Gounko, Iouri (My University, 2010)
Quantum dot (QD) nanoclusters were formed using oppositely charged colloidal CdTe QDs, of two different sizes, mixed in aqueous solutions. The photoluminescence (PL) spectra and time-resolved PL decays show signatures of Forster resonant energy transfer (FRET) from the donor QDs to the acceptor QD in the nanoclusters. A concentration dependence of the donor QD lifetime is observed in mixed solutions with a donor: acceptor ratio greater than 1:1. The concentration dependent time-resolved PL data indicate different regimes of cluster formation, with evidence for donor-to-donor FRET in the larger donor-acceptor nanoclusters and evidence for the formation of all-donor clusters in mixed solutions with high donor concentrations.
PUBLISHED
Keywords: Optics; Quantum dot (QD) nanoclusters; Nanoscience & Materials; Smart & Sustainable Planet